Relationship between menarche and the beginning of sports - Bugaevsky, K. A.; Anatolyevich, B. K. (International Clinical and Medical Case Reports, 2023)
The article presents the materials of a study devoted to the question of the possible relationship between the timing of the menarche and the start of active sports. The data of different authors and the opinions of researchers on the issue under study are given. The author's materials are presented on a longitudinal study on the relationship between the timing of the menarche and the dynamics of sports activities in athletes of puberty and adolescence.